Cellulographics: A novel smartphone user classification metrics - Prateek Kalia; Yogesh Kumar Dwivedi; Ángel Acevedo-Duque (Journal of Innovation & Knowledge (JIK), 2022)
Despite the worldwide surge in smartphone use, there are no classification metrics based on its use. In this article, a comprehensive concept called 'Cellulographics' is introduced for characterization of smartphone users, which includes behavioral classification based on user characteristics like smartphone experience (SE), smartphone use skill (SUS), smartphone internet experience (SIE), smartphone use periods (SUP), smartphone screen time (SST), smartphone use frequency (SUF), smartphone use activities (SUA), and smartphone use location (SUL). This concept can be applied to any field of study without limitations, where smartphone use is involved.
Keywords: 650; Experience; Internet; Location; Screen time; Smartphone; Use frequency